The Political Economy of Conditional and Unconditional Foreign Assistance : Grants vs. Loan Rollovers - Mayer, Wolfgang (IMF Working Papers; Working Paper ;, 2004)
Improving the effectiveness of financial assistance programs is a priority of international financial institutions (IFIs). This paper examines the effectiveness of alternative assistance instruments in a dynamic political economy framework. Economic policies of the receiving country are distorted by the influence of a domestic interest group. The assistance-providing IFI aims at reducing these distortions. The IFI provides assistance either as grants or loans, and either conditionally on reducing policy distortions or unconditionally. The paper shows that, other things constant, one-time grants are more effective than loan rollovers when assistance is unconditional, but that the opposite is true when assistance is conditional.